Effects of urbanization on the diversity, life-history traits and fluctuating asymmetry of odonates (Odonata: Zygoptera and Anisoptera) - Silva, Henrique Venâncio (2022)
Urbanization has grown progressively and changing drasticly and rapidly natural habitats, threatening the viability of sensitive groups. Little is known about the diversity and taxonomy of dragonflies from urban areas of the Cerrado, although some studies show that this environment can contribute to filling Linnean and Wallacean gaps. In addition, studies on the plastic responses of odonates under urbanization and extreme climate events are still emerging and rare in the Neotropical region. In this thesis, we investigated how urbanization can affect diversity and plastic responses of odonates, both for local urban conditions and future climate events. To achieve these objectives, we first performed an extensive inventory of the group in various ecosystems and phytophysiognomies of the Cerrado in urban and non-urban areas between 2018 and 2020 in Uberlândia, Minas Gerais. This inventory composed the first chapter. From these samples we separated two damselflies species (Acanthagrion truncatum Selys, 1876 and Argia reclusa Selys, 1865), representing different ecosystems, and that are abundant among urbanization gradients and within urban areas. These samples were part of the second chapter, which aimed to evaluate the morphometric and stress responses (evaluated by fluctuating asymmetry) of the group\'s wings in under urbanization, more specifically to fragmentation, and local preservation of urban fragments. Finally, in the third chapter, we conducted an experiment with larvae to verify the effect of future heat waves on A. truncatum life history traits, sampled in urban pons. In the first chapter, we described the female of Forcepioneura machadorum Vilela, Venâncio & Santos, 2020 (Coenagrionidae: Protoneurinae) and sampled 101 species in urban and non-urban areas of Uberlândia, eight of these were new records for Minas Gerais. In the second chapter, we helped to fill knowledge gaps about the effects of urbanization on morphological traits and asymmetry of damselflies along urbanization gradients. For A. truncatum, we observed a negative effect on wing size, while the preservation of urban fragments proved to be an important factor for the size and shape of this trait for A. reclusa. Finally, we demonstrate in the third chapter that exposure of larvae to heat waves results in phenological advance and reduction in the size of urban adults of A. truncatum, a pattern that can affect the future viability of this species in this type of land use. Thus, the results of this thesis showed that we still know little about how urbanization can affect diversity and plastic and ontogenetic responses of odonates. Especially in the Neotropical region, where urbanization and climate change come too much and quickly growing, there is the urgency of further studies of the group.